Work-life balance and male lawyers: a socially constructed and dynamic process - Boiarintseva, G.; Richardson, Julia (EMERALD GROUP PUBLISHING LTD, 2019)
© 2019, Emerald Publishing Limited. Purpose: The purpose of this paper is to theorize men’s experiences of work-life balance in male-dominated, high-performance industries. Design/methodology/approach: This study provides an in-depth qualitative study comprising interviews and informal conversations with male lawyers in Canada. Findings: This study highlights the socially constructed nature of male lawyers’ experiences of work-life balance and the recursive impact of industry, professional and societal expectations and norms. Research limitations/implications: A relatively small sample size, suggesting the need for further study with a larger and more diverse sample. The study was conducted in Canada – other national contexts may furnish different results. Practical implications: This study identifies the need for greater awareness of how institutional, professional and societal expectations and norms impact on men’s experiences of work-life balance in male-dominated, high-performance industries. Social implications: This paper indicates that greater attention needs to be paid to work-life balance among men in male-dominated, high-performance industries. Originality/value: This paper explores men’s experiences of work-life balance in a male-dominated industry within an interpretivist paradigm.